Important methods of improving listening skills and Easy ways to understand English topics - Isayeva Mashhura Murotaliyevna (Genius Journals, 2023)
In this article, it is stated about how to develop listening skill for foreign language learners besides this, students can understand a various topics if they want to speak fluently
Keywords: Avoid interrupting; pay attention; clarify and summarize